The almanac investor : - Hirsch, Jeffrey A. (Wiley, 2006)
The key to successful financial research is the ability to access and manipulate accurate data. This book, and its cutting edge, completely Internet-based trading system--that can organise and evaluate any market data, with all parameters set by the researcher--introduces a new way of doing just that. The Hirsch name is known for time tested and successful research and analysis, and The Almanac Investor will share valuable Hirsch theories and strategies with investors.